Resistencia de plantas Café Arábico (Coffea arabica) variedad ‘Caturra Roja’ a la Roya Amarilla (Hemileia vastatrix), en la Región San Martín - Vallejos Orbe, Jhon Patrick (2016)
Coffee is a crop of great importance on a global scale and in Peru is one of the main generators of foreign exchange since the nineteenth century. Its production in Peru and Latin America is based mainly on the species Coffea arabica L., which produces a drink with a mild aroma and flavor. The San Martin region has more than 92 thousand hectares of coffee, which represent the economy of 35 thousand families that are dedicated to the production; 95% of the coffee plantations of San Martín are conventional and 5% represents the organic production of the area. These areas have been affected by coffee rust which is a disease that seriously limits the production of C. arabica; Their presence is determined by climatic conditions, since high relative humidity is necessary for sporulation and spore dispersion, but their genetic resistance is the main form of control of the pathogen and has been transferred to commercial varieties of C. arabica a Through the Timor hybrid (C. arabica and C. canephora). The most common varieties that were affected by rust are 'Caturra' and 'Typical' and to a lesser extent the 'Catimor' variety. Caturra red, is one of the main varieties cultivated in the San Martín region that was affected by rust, but it is a variety with good organoleptic characteristics in fragrance, aroma and flavor (quality coffee), (Estrella, 2015); Which makes this variety that has high demand in the foreign market; The Peruvian Amazonian Research Institute (IIAP-T) has set out to develop a research project to identify and produce vegetative material of the rust-resistant red caturra variety. With this proposal, rust-tolerant "red caturra" maize seedlings selected from Altitude 1 (800 - 1 000 msnmm) and Altitude 2 (1) 001 - 1,200 msnmm) for its evaluation of resistance to rust in nursery. The evaluation of the rust resistance of the coffee tree yielded results in which plants from Altitude 2 (1 001-1 200 msnmm) presented better characteristics such as height (figure 1), production of main leaves (figure 5) and Production of axillary leaves (Figure 7) in coffee rust resistance